2010
DOI: 10.1039/b9py00301k
|View full text |Cite
|
Sign up to set email alerts
|

Living spontaneous gradient copolymers of acrylic acid and styrene: one-pot synthesis of pH-responsive amphiphiles

Abstract: RAFT polymerization was used to prepare copolymers of acrylic acid (AA) and styrene (STY) with mole fractions of STY (F STY ) ranging from 0.1 to 0.3 and targeted degrees of polymerization between 50 and 150. The high reactivity of AA-terminal radicals towards STY in this system (r AA ¼ 0.082) resulted in the spontaneous formation of composition gradients, resulting in polymers with block-like structures comprising a STY-rich segment, a relatively short transitional segment, and a segment of AA homopolymer. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 29 publications
1
91
0
2
Order By: Relevance
“…The integrated copolymerization equation was fitted to conversion, monomer fraction and copolymer composition data, assuming non‐negligible errors in all variables. As noted before,1, 21 this method is computationally inefficient but simple to implement in the conventional Microsoft Excel 2003 software 1. The instantaneous copolymer composition at various conversions was determined from the individual monomer to polymer conversions estimated by 1 H‐NMR, which, in general, showed that MA was consumed much more rapidly than VAc.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The integrated copolymerization equation was fitted to conversion, monomer fraction and copolymer composition data, assuming non‐negligible errors in all variables. As noted before,1, 21 this method is computationally inefficient but simple to implement in the conventional Microsoft Excel 2003 software 1. The instantaneous copolymer composition at various conversions was determined from the individual monomer to polymer conversions estimated by 1 H‐NMR, which, in general, showed that MA was consumed much more rapidly than VAc.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed and consistent kinetic investigations of controlled radical polymerizations can be a time‐consuming and demanding task when carried out using traditional experimental techniques 1–3. This is mainly due to the fact that radical polymerizations can be very susceptible towards oxygen traces present in the reaction mixtures 4, 5.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…use of the literature data on copolymerization in bulk (r styrene = 0.21 and r AA = 0.08) [16] and in DMF (r styrene = 1.03 and r AA = 0.4) [17] as well as the relative activities of the monomers calculated from the exper imental data obtained in this study via the KelenTüdös method for the copolymerization of styrene and AA in bulk in the presence of BB (r styrene = 0.31 and r AA = 0.05). The copolymer prepared via copolymer ization in bulk is more enriched with AA units than the copolymer prepared in DMF.…”
Section: Copolymerization Of Styrene With Acrylic Acid Mediated By Ramentioning
confidence: 99%